(untitled) (American Journal of Business Management, Economics and Banking, 2023)
When joining the WTO, the existing phytosanitary requirements in the Republic of Uzbekistan will have to be harmonized with the international phytosanitary requirements of this international organization. The State Plant Quarantine Inspectorate of the Republic of Uzbekistan must comply with the “Agreement on the Application of Sanitary and Phytosanitary Measures” introduced by the WTO organization. Phytosanitary requirements should have a "technical basis".